Islamic festivals - Knight, Khadijah (Crystal Lake, IL : Heinemann Library, 1997)
Introduces the festivals celebrated in the Islamic faith.
Includes bibliographical references (p. 46) and index.
Elem. School Library Collection.
5.5
5-8
Keywords: Fasts and feasts -- Islam -- Juvenile literature; Festivals -- Islamic countries -- Juvenile literature; Islam -- Customs and practices -- Juvenile literature; Rites and ceremonies -- Islamic countries -- Juvenile literature; Fasts and feasts -- Islam; Festivals -- Islamic countries; Islam -- Customs and practices; Muslims -- Social life and customs; Rites and ceremonies -- Islamic countries; Festivals -- Islamic countries; Islam; Islamic holidays; Muslims -- Social life and customs; Rites and ceremonies -- Islamic countries